Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Kesehatan Reproduksi Remaja Pada Siswi Kelas VIII Di SMP Negeri 28 Semarang - Pungky Ristraningsih, Galang, Dr. Faizah Betty Rahayuningsih A., S.Kep, M.Kes (2017)
The most important health in adolescence is reproductive health. Adolescent reproductive health program is to help teens to have knowledge, awareness, attitudes and behavior of healthy reproductive life is responsible, through advocacy, promotion, IEC, counseling and services to adolescents who have special problems. Adolescent reproductive health includes aspects of teenage life related knowledge, attitudes and sexual behavior and family life. The purpose of this study was to determine the level of reproductive health knowledge before and after health education and to determine whether there is influence of health education on adolescent reproductive health knowledge level in grade VIII SMP Negeri 28 Semarang. This research method is a pre-experimental research design with one group pre-post test design. This research was conducted at SMPN 28 Semarang in March 2017. Samples taken as many as 57 students of class VIII with propotional simple random sampling technique. The instrument used was a questionnaire of adolescent reproductive health knowledge by using the media and poster presentations. Test to determine the data analysis using non-parametric Wilcoxon test. Results of research addressing -rata average grade VIII level of knowledge before being given health education on adolescent reproductive health is at 1.84 and the average - average class VIII student knowledge after health education given at 2:58 with a significant value of 0.000 or P <0.05. The conclusion shows the influence of health education on adolescent reproductive health knowledge level in grade VIII SMP Negeri 28 Semarang.